Towards Health Workplace Environment: Managing the Antecedents and Consequences of Job Stress in Saudi Arabia - El-Shafie, Elham; Nassani, Abdelmohsen A.; Bin Saif, Abeer (The Arab Journal of Administration, 2024)
This study investigates the variables influencing antecedents and consequences of job stress in Saudi Arabia. The relationships between work-related stress, burnout, overload, work-family conflict, job satisfaction, and turnover intention, were investigated directly and indirectly. All of the study’s participants, who are directly affected by these variables, are workers in the capital city of Saudi Arabia. There were two hundred individuals in the random sample. The statistical tools used in this study are (AMOS) and (SPSS). The results of this study show most clearly that work overload positively and significantly influences job stress. Second, job stress positively and significantly influences work-family conflict. Third, job stress negatively influences job satisfaction. Fourth, Job satisfaction negatively influences turnover intention. Fifth, work-family conflict positively and significantly influences turnover intention. These findings indicate that Job stress frequently arises from incongruous job responsibilities, resulting in a physiological and emotional reaction to job demands that surpass a worker’s capabilities or resources. Stress can hinder concentration, decision-making, and problem-solving abilities, reducing work performance. Work-family conflict occurs when work demands clash with family obligations, creating challenges in fulfilling both responsibilities. Job satisfaction fosters solid emotional connections and cultivates loyalty towards the company. Individuals experiencing significant work-family conflict frequently express a desire to resign from their current employment, thus emphasizing the intricate connection between job-related stress, conflict, and loyalty.